PENGARUH PENGGUNAAN TEKNOLOGI DALAM PEMASARAN PARIWISATA SELAMA MASA PANDEMI COVID-19 DI INDONESIA - Iswanto, Dedy; Amol, Febriyanti; Sangadji, Suwandi S.; Halawa, Forman (Universitas Nusa Cendana, 2024)
Technology has an important role to play in advancing sustainable tourism destinations. The purpose of this study is to determine the effect of technology on tourism marketing during the COVID-19 pandemic in Indonesia which can be used as material for decisions by tourism practitioners and is useful for researchers in the tourism sector. This research was conducted using a systematic literature review (SLR) of 2 reference articles from Scopus. The results show that there is no antecedents from tourism marketing that were studied during the COVID-19 pandemic. In addition, there is a positive influence of technology on tourism marketing during the COVID-19 pandemic. There are several consequences of technology adoption in tourism marketing, namely image, trust, visitors' interest and tourist behavior. However, this research still has limitations on the reference sources used (only Scopus), it is recommended to add a database for future researchers and add other research problem formulations. Keywords: Technology ; Tourism Marketing ; COVID-19 pandemic